Severe Epidermal Nerve Fiber Loss in Diabetic Neuropathy Is Not Reversed by Long-Term Normoglycemia After Simultaneous Pancreas and Kidney Transplantation - Havrdova, T; Boucek, P; Saudek, F; Voska, L; Lodererova, A; Üçeyler, N; Vondrova, H; Skibova, J; Lipar, K; Sommer, C (American journal of transplantation, 2016)
Whether nerve fiber loss, a prominent feature of advanced diabetic neuropathy, can be reversed by reestablishment of normal glucose control remains questionable. We present 8-year follow-up data on epidermal nerve fiber (ENF) density and neurological function in patients with type 1 diabetes after simultaneous pancreas and kidney transplantation (SPK) with long-term normoglycemia. Distal thigh skin biopsies with ENF counts, vibration perception thresholds (VPTs), autonomic function testing (AFT) and electrophysiological examinations were performed at time of SPK and 2.5 and 8 years after SPK in 12 patients with type 1 diabetes. In comparison to controls, baseline ENF density, VPT and AFT results of patients indicated severe neuropathy. At follow-up, all SPK recipients were insulin independent with excellent glycemic control and kidney graft function; however, the severe ENF depletion present at baseline had not improved, with total ENF absence in 11 patients at 8-year follow-up. Similarly, no amelioration occurred in the VPT and AFT results. Numerical improvement was seen in some electrophysiological parameters; however, statistical significance was achieved only in median motor nerve conduction velocity. ENF loss and functional deficits in advanced diabetic peripheral neuropathy are rarely reversible, even by long-term normoglycemia, which underscores the importance of neuropathy prevention by early optimal glycemic control.
Keywords: diabetes: secondary complications; diabetické nefropatie; diabetes mellitus 1. typu; pancreas/simultaneous pancreas-kidney transplantation; Male; Postoperative Complications; Graft Survival; transplantace slinivky břišní; Risk Factors; neurology; Glomerular Filtration Rate; následné studie; prognóza; clinical research/practice; Pancreas Transplantation; mužské pohlaví; pooperační komplikace; kůže; Graft Rejection; diabetes: type 1; nervová vlákna; Nerve Fibers; Kidney Function Tests; Follow-Up Studies; Diabetic Nephropathies; lidé; ženské pohlaví; Skin; Kidney Transplantation; transplantace ledvin; Humans; rejekce štěpu; přežívání štěpu; vyšetření funkce ledvin; rizikové faktory; endocrinology/diabetology; Prognosis; Diabetes Mellitus, Type 1; hodnoty glomerulární filtrace; Female; lidé středního věku; Middle Aged